Biofouling control: the impact of biofilm dispersal and membrane flushing. (15th June 2021) - de Vries, Hendrik J.; Kleibusch, Eva; Hermes, Gerben D.A.; van den Brink, Paula; Plugge, Caroline M.
Highlights Biofouling removal: stop, flush and go: Nutrient limitation leads to multispecies biofilm dispersal from membranes Biomass removal is a result of the stop period and the flow velocity of the flush Repetitive membrane cleaning increases the mechanical resistance of the biofilm Repetitive cleaning leads to a stable, resilient bacterial community on the membrane Abstract: Pure culture studies have shown that biofilm dispersal can be triggered if the nutrient supply is discontinued by stopping the flow. Stimulating biofilm dispersal in this manner would provide a sustainable manner to control unwanted biofilm growth in industrial settings, for instance on synthetic membranes used to purify water. The response of multispecies biofilms to nutrient limitation has not been thoroughly studied. To assess biomass dispersal during nutrient limitation it is common practise to flush the biofilm after a stop-period. Hence, flow-stop-induced biomass removal could occur as a response to nutrient limitation followed by mechanical removal due to biofilm flushing (e.g. biofilm detachment). Here, we investigated the feasibility to reduce membrane biofouling by stopping the flow and flushing the membrane. Using a membrane fouling simulator, biomass removal from synthetic membranes after different stop-periods was determined, as well as biomass removal at different cross flow velocities. Biomass removal from membrane surfaces depended on the nutrient limiting period and on the flow velocity during the biofilm flush. When flushed at a low flow velocity (0.1 m.s −1 ), the duration of the stop-period had a large effect on the biomass removal rate, but when the flow velocity was increased to 0.2 m.s −1, the length of the stop period became less considerable. The flow velocity during membrane flushing has an effect on the bacterial community that colonized the membranes afterwards. Repetition of the stop-period and biofilm flushing after three repetitive biofouling cycles led to a stable bacterial community. The increase in bacterial community stability coincided with a decrease in cleaning effectivity to restore membrane performance. This shows that membrane cleaning comes at the costs of a more stable bacterial community that is increasingly difficult to remove. Graphical abstracts: Graphical abstracts Image, graphical abstract